VD_FINDINFO Décision / 2014 / 10 vom 14. Januar 2013 - VD Tribunal cantonal (2013)
INDEMNITÉEN GÉNÉRAL, ACQUITTEMENT, PRÉVENU, CLASSEMENT DE LA PROCÉDURE, TARIFEN GÉNÉRAL | 45 al. 1 LPAv, 429 al. 1 let. a CPP (CH)